Analysis of Student Errors in Relation and Function Materials for Class VIII SMP Negeri Pandawai - Nuhamara, Yuliana Tamu Ina; Hunggujawa, Yohbet; Nggaba, Mayun Erawati; Randjawali, Erwin; Eko, Yuliana S.; Sanit, Irna N. (Journal of Educational Sciences, 2022)
This study has several objectives, obtaining a description of the characteristics of student errors, as well as factors that cause students of class VIII of State Junior High School to make mistakes in the settlement of relationships and functions. This type of research is qualitative descriptive. Class VIII students with a total of 27 people are the research subject. The technique in determining the research subjects is the purposive sampling technique. Data collection with written test techniques, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and data verification. Validity of data with triangulation of techniques and sources. The results of this study showed that students made 5 types of mistakes made by students on the settlement of relationships and fungi, namely mis-understanding of the concept of 19 students, errors in the use of data of 14 students, errors in interpreting the language of 18 students, technical errors of 26 students, and errors in the conclusion of 21 students. The factors that cause students to make mistakes in solving relationships and functions come from internal and external factors.